The Effect Of Non-Performing Financing, Financing To Deposit Ratio And Return On Assets On Mudharabah Financing - Chandra Triyantono, Irvan; Rahmanti, Virginia Nur (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
This quantitative study analyzes the effects of Non-Performing Financing (NPF), Financing-to-Deposit Ratio (FDR), and Return on Assets (ROA) on mudarabah financing in Islamic commercial banks listed on the Indonesia Stock Exchange during the 2021-2024 period. From a population of four banks, two were selected as samples using purposive sampling. The data were analyzed using descriptive statistics and linear regression with a bootstrapping approach. The results indicate that Non-Performing Financing (NPF) and Return on Assets (ROA) do not affect mudarabah financing, while the Financing-to-Deposit Ratio (FDR) has a negative and significant effect on mudarabah financing. Simultaneously, Non-Performing Financing (NPF), Financing-to-Deposit Ratio (FDR), and Return on Assets (ROA) affect mudarabah financing. These findings do not fully support asymmetric information theory and financial intermediation theory but confirm that intermediation effectiveness, risk management, and profitability jointly determine banks’ capacity to distribute profit-sharing financing, particularly mudarabah financing.